Neurosurgical management of severe Traumatic Brain Injury (TBI) (Research, Society and Development, 2025)
Severe traumatic brain injury (TBI) represents an important cause of morbidity and mortality worldwide, being responsible for a high number of hospitalizations in intensive care units and for permanent neurological consequences. This review aims to analyze the main surgical interventions used in the management of severe TBI, addressing their indications, techniques, clinical outcomes and contemporary challenges. Among therapeutic strategies, neurosurgical management plays a fundamental role in reducing intracranial pressure (ICP), controlling expansive lesions and preventing secondary cerebral lesions. The main surgical indications include intracranial hematomas (epidurais, subdurais, intraparenchymatous), refractory cerebral edema and imminent hernia sinais. Decompressive craniectomy has been consolidated as a key procedure in cases refractory to clinical treatment, its impact on functional prognosis is still subject to debate in the literature. Recent studies emphasize the importance of continuous ICP monitoring, use of evidence-based protocols and individualization of the surgical approach. This review seeks to critically analyze the current neurosurgical procedures in severe TBI, highlighting indications, techniques used, clinical results and future perspectives in an attempt to optimize the care of these complex patients.